IMPLEMENTATION OF QR CODES ON ICHIBAN SUSHI RESTAURANT'S DISH MENU ON ORDER TIME EFFICIENCY AND CUSTOMER SATISFACTION LEVEL - Firstarine Alberlianasari; Salma Nabilah; Safrina Dewi Rahmawati (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This research aims to find out how the QR code affects the efficiency of consumer ordering time and the level of consumer satisfaction with the QR code. This is a qualitative research which describes the QR code research on the Ichiban Sushi restaurant menu. Data collection techniques using observation and interviews. The research carried out on "Ichiban Sushi" restaurant which is located in Plaza Asia, Tasikmalaya City in West Java. The results of this study focus on solving problems by simplifying the queue management process for the Ichiban Sushi menu and simplifying restaurant menu ordering and how it affects customer satisfaction. The findings reveal that there was an efficiency in ordering time because using this QR code was felt to be faster and more flexible, consumers could order simultaneously and consumers also did not need to queue to order restaurant menus. QR codes on the ordering menu for Ichiban Sushi Restaurant greatly affects the level of consumer satisfaction, where the majority of consumers feel satisfied with the use of QR codes on the ordering menu for Ichiban Sushi Restaurant which is certainly very beneficial for consumers.